1994
DOI: 10.1080/01919519408552381
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofGiardia murisUsing Ozone and Ozone-Hydrogen Peroxide

Abstract: The disinfection effects of the ozone molecule alone and that of ozone decomposition products when inactivating Giardia muris cysts were investigated at bench-scale using two different ozone demand-free laboratory buffer systems. The first water was a 0.05 M phosphate buffer with hydrogen peroxide added at a 10:1 weight ratio. The second water was a 0.05 M phosphate -0.01 M bicarbonate buffer which quickly scavenged radical species from ozone decomposition. The C3H/HeN mouse model was used to assess the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…() and Labatiuk et al . () also reported that direct reaction with molecular ozone is more effective for inactivation of micro‐organisms than reaction with radicals arising from decomposition of ozone molecules. Second, the combination effect of ozone with low pH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…() and Labatiuk et al . () also reported that direct reaction with molecular ozone is more effective for inactivation of micro‐organisms than reaction with radicals arising from decomposition of ozone molecules. Second, the combination effect of ozone with low pH.…”
Section: Discussionmentioning
confidence: 97%
“…Ozone is more stable at low than at high pH (Khadre et al 2001), which means direct reaction with ozone molecules accounts for the majority of pathogen inactivation in low pH apple juice. Finch et al (1992) and Labatiuk et al (1994) also reported that direct reaction with molecular ozone is more effective for inactivation of micro-organisms than reaction with radicals arising from decomposition of ozone molecules. Second, the combination effect of ozone with low pH.…”
Section: Discussionmentioning
confidence: 99%
“…It has not been well established whether molecular ozone, the radical species or both are responsible for inactivation of microorganisms. Some researchers have suggested that direct reaction with molecular ozone is the predominant mechanism for inactivation of microorganisms, e.g., E. coli, (Finch et al, 1992;Labatiuk et al, 1994;Hunt and Marinas, 1997) while others suggest indirect reactions with radicals to be responsible for inactivation (Bancroft et al, 1984). It is likely that the relative importance of direct and indirect reactions with ozone in determining microbial inactivation responses will vary between microorganisms.…”
Section: Mechanism Of Microbial Inactivationmentioning
confidence: 99%
“…Halogens (chlorine‐releasing agents and iodine) and ozone are the disinfectants of choice for ridding water supplies of viable cysts, a highly important role when it is considered that only one cyst is required to produce an infection (Jarroll 1988, 1999; Fraker et al . 1992; Labatuik et al . 1994).…”
Section: Differentiation In Protozoa and Susceptibility To Antimicrobmentioning
confidence: 99%